The effective characteristics of an urban park through visitors perception case study: KLCC Park / Farah Amira Ahmad Shafee and Siti Mazwin Kamaruddin - Ahmad Shafee, Farah Amira; Kamaruddin, Siti Mazwin (Faculty of Architecture, Planning and Surveying, 2019)
In industrializing and urbanizing countries such as Malaysia, urban parks play an increasingly important role in contributing to the quality of urban life and environment. The main aim of this study is to evaluate the effective characteristics of an urban park and the implementation of park management by the private organization at KLCC Park towards increasing the value of life for people living in the city. The objective of this study is to gain an insight into visitors' perception of the effectiveness of the KLCC Park and an overview of the park management by KLCC Park. This study used a mixed methodology approach. This research used questionnaires as the instrument to record respondents' perspectives and conducted an interview with a key manager of KLCC Park Management. There were 320 respondents who participated in this study. The study involved a comprehensive literature research on the criteria of urban park effectiveness, passive engagement opportunities and active engagement opportunities, accessibility and safety. The benefits received by the visitors play an important role towards the effectiveness of the place. The results of the study indicate that urban park is receiving increasing attention from visitors, but that planning and management are still not optimal. The finding in term of planning and management of the park can conclude that urban planners and green space managers need to ensure that green spaces meet the demands and preferences of visitors and institutional structures are important for sound green space planning and management. Kuala Lumpur City Centre (KLCC) Park, offers a calm and harmonious environment in the midst of the hustle and bustle of a busy and dynamic city and dissipating the tensions of city living. It was concluded that the criteria of comfort felt by the visitors were very important to the assessment of an effective urban park.